Removal of pollutants from an AMD from a coal mine by neutralization/precipitation followed by “in vivo” biosorption step with the microalgae Scenedesmus sp. - Santos, Karine Batista dos (2020)
This work evaluates the benefits of a complementary treatment step of acid mine drainage (AMD) using the algae Scenedesmus sp. in terms of algae biomass production, residual metal removal, and the toxicity of the discharged water. Conventional treatment by neutralization/precipitation of an AMD from a coal mine in Brazil was conducted with Ca(OH)2 at pH 8.7. Algal growth studies were performed in the treated AMD, with and without a nutrient supply. The raw e uent and treatments were compared in terms of residual concentration of metals and sulfate, conductivity, and toxicity with the Allium cepa and Daphnia magna test organisms. The results show that the conventional treatment allowed a major metal removal, reduction in the conductivity, and good indices in the toxicological parameters evaluated. The biosorption with in vivo microalgae improved the quality of the e uent for residual metals. No significant toxicity was observed to Allium cepa in all treatments performed, while the Daphnia magna test indicated a reduction in toxicity after the biosorption step. It was concluded that algae growth can be carried out in treated mine waters, providing algae biomass and helping to achieve the standards for water discharge.